2021
DOI: 10.21037/hbsn-21-260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice of transarterial chemoembolization for hepatocellular carcinoma: consensus statement from an international expert panel of International Society of Multidisciplinary Interventional Oncology (ISMIO)

Abstract: Importance: Transarterial chemoembolization (TACE) has been associated with a wide range of practice variations for hepatocellular carcinoma (HCC) between the East and the West. This considerable ambiguity may lead to the heterogeneous quality in treatment and have a negative impact on the role of TACE in the overall multidisciplinary HCC treatment system.Objective: It may be a good start to establish a guideline worldwide to have this consensus from experts who represent east and west, although it does not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 61 publications
(60 reference statements)
1
47
0
Order By: Relevance
“…In theory, BACE could block the arterial blood flow and increase drug concentration at tumor sites, which may improve the prognosis of MWA. Similar effectiveness has already been shown and recommended in liver cancers treated with TACE and thermal ablation ( 18 , 19 ). Liu et al.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…In theory, BACE could block the arterial blood flow and increase drug concentration at tumor sites, which may improve the prognosis of MWA. Similar effectiveness has already been shown and recommended in liver cancers treated with TACE and thermal ablation ( 18 , 19 ). Liu et al.…”
Section: Introductionsupporting
confidence: 74%
“…In theory, BACE could block the arterial blood flow and increase drug concentration at tumor sites, which may improve the prognosis of MWA. Similar effectiveness has already been shown and recommended in liver cancers treated with TACE and thermal ablation (18,19). Liu et al (20) indicate that combined treatment with DEB-TACE has advantages in improving the prognosis of early-stage liver cancer compared to MWA alone.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The guidelines recommend that patients start receiving systemic therapy once they are diagnosed with TACE refractoriness ( 6 , 8 , 9 ). However, a recent international expert panel of International Society of Multidisciplinary Interventional Oncology consensus statement and a survey by Chinese College of Interventionalists indicated that repeated TACE especially TACE based combination therapy can also achieve survival benefit in patients refractory to TACE ( 32 35 ). Meanwhile, PD-1 inhibitors have been increasingly explored as representative agents for immunotherapy, the possible mechanism underlying the benefit of TACE combined with a PD-1 inhibitor was revealed: TACE could decrease the ratio of CD4+/CD8+ cells and increase the level of PD-1 mRNA expression in patients with HCC ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single treatment is frequently insufficient to achieve a satisfactory curative effect. More and more patients are opting for a multidisciplinary combination treatment ( 28 ). TACE treatment is an integral part of this multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%